Epithelial Cell Polarity During Drosophila Midgut Development - Chen, Jia; St Johnston, Daniel (Frontiers in Cell and Developmental Biology, 2022)
The adult Drosophila midgut epithelium is derived from a group of stem cells called adult midgut precursors (AMPs) that are specified during the migration of the endoderm in early embryogenesis. AMPs are maintained and expanded in AMP nests that lie on the basal side of the larval midgut throughout the larval development. During metamorphosis, the larval midgut undergoes histolysis and programmed cell death, while the central cells in the AMP nests form the future adult midgut and the peripheral cells form the transient pupal midgut. Here we review what is known about how cells polarise in the embryonic, larval, pupal and adult midgut, and discuss the open questions about the mechanisms that control the changes in cell arrangements, cell shape and cell polarity during midgut development.